OHP-036 Evaluation of Antibiotic Appriopriateness and Use in Imola Hospital. (12th March 2013) - Silvani, MC; Paternoster, L; Calabria, S; Martens, I; Gambetti, S
Abstract : Background: Misuse of antibiotics in hospitals may cause bacterial resistance as well as increased costs and unnecessary exposure of patients to drugs. Purpose: To evaluate antimicrobial consumption and appropriateness through a new antibacterial stewardship policy. Materials and Methods: The study was carried out in Imola Hospital (Bologna) and 2009–2011 drug consumption data were obtained from the pharmacy service. Data were analysed by clinical area and single wards and were expressed by ATC classification and defined daily doses per 100 bed-days (DDD). A form for personalised antibacterial treatment (ATf), including diagnosis and documented reasons for the choice of antibiotic, was introduced for levofloxacin, teicoplanin, meropenem, linezolid, tigecycline and daptomycin. Results: In 2011, overall antibacterial consumption was 78 DDD (+4% vs. 2010); the major increase was observed in medical units (MED: +9%) and paediatric/gynaecological units (+6%). Intensive care units/emergency department (ICUs/EDs) and surgical units (SUR) exhibited a decrease in consumption (−13%, −7%, respectively). The use of critical antimicrobial agents decreased: fluoroquinolones (19 DDD, −15%), carbapenems (3.5 DDD, −18%) and glycopeptides (3.1 DDD, −17%). The introduction of ATfs (May 2011) contributed to a decrease in the consumption of antibiotics (e.g. MED: 75 DDD semester I vs. 71 DDD semester II 2011; overall 2011: 73 DDD). The analysis of ATfs shows that critical antibacterial agents were mainly prescribed to treat respiratory tract infections (MED: 58%, ICU/ED: 44%, SUR 30%), urinary tract (MED e ICU/ED: 20%), skin and soft tissues (SUR: 35%, ICU/ED: 16%, MED: 6%) and intra-abdominal infections (SUR: 9%). Levofloxacin (55%) and meropenem (11%) were the most prescribed for respiratory tract infections, teicoplanin (6%) for skin and soft tissue infections. Conclusions: Our stewardship policy led to a reduction in the use of wide-spectrum antibiotics, so ATf may represent a valid method of rationalising the choice of antimicrobial treatment. Acknowledgements: Agenzia Italiano Del Farmaco, Emilia Romagna Region. No conflict of interest.